2015
DOI: 10.1080/14616734.2015.1042487
|View full text |Cite
|
Sign up to set email alerts
|

Assessing both safe haven and secure base support in parent–child relationships

Abstract: Although the attachment construct refers to a child's tendency to use an attachment figure both as a safe haven in times of distress as well as a secure base from which to explore, approaches to assessing attachment at older ages have focused on safe haven behavior. We tested modified versions of the Friends and Family Interview and the Security Scale Questionnaire to examine separately the correlates of safe haven and secure base support from parents. The main study (n = 107 children, 10-14-year-olds) include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
99
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 30 publications
8
99
0
3
Order By: Relevance
“…Our findings suggest that, when using the MCAST stems with father doll, the task may equally capture the child's safe haven and secure base functioning, as the core feature of the attachment system (Waters & Cummings, ), indicating that the MCAST yields a “secure attachment” factor for father administration, as it does for mother administration. Our results are in line with previous studies suggesting at least partial concordance between mother‐child and father‐child attachment (Bacro & Florin, ; Booth‐LaForce et al , ; Di Folco et al , ; Diener et al , ; Kochanska & Kim, ), as well as with recent evidence that both mothers and fathers are regarded as secure base and safe haven (Kerns, Mathews, Koehn, Williams & Siener‐Ciesla, ). Moreover, our findings are in line with findings reported by Barone and Lionetti () and Green et al (), suggesting that the factor explaining most variance in MCAST subscale scores concerned attachment security and coherence.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings suggest that, when using the MCAST stems with father doll, the task may equally capture the child's safe haven and secure base functioning, as the core feature of the attachment system (Waters & Cummings, ), indicating that the MCAST yields a “secure attachment” factor for father administration, as it does for mother administration. Our results are in line with previous studies suggesting at least partial concordance between mother‐child and father‐child attachment (Bacro & Florin, ; Booth‐LaForce et al , ; Di Folco et al , ; Diener et al , ; Kochanska & Kim, ), as well as with recent evidence that both mothers and fathers are regarded as secure base and safe haven (Kerns, Mathews, Koehn, Williams & Siener‐Ciesla, ). Moreover, our findings are in line with findings reported by Barone and Lionetti () and Green et al (), suggesting that the factor explaining most variance in MCAST subscale scores concerned attachment security and coherence.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, it has been shown that children and adolescents with a secure attachment to parents report higher levels of psychological well-being and life satisfaction (Armsden and Greenberg 1987;Nickerson and Nagle 2004) and higher levels of self-esteem (Pinto et al 2015), use more adaptive emotion regulation strategies (Kerns et al 2007;Sroufe 2005), present greater academic and peer competence at school (Kerns et al 2015), and establish more positive relationships with their peers (Berlin et al 2008;Schneider et al 2001;Sroufe 2005). Several studies have also shown that an insecure attachment relationship with parents increases the risk of developing internalizing and externalizing disorders (Fearon et al 2010;Groh et al 2012;Kerns et al 2011;Kerns and Brumariu, 2014;O'Connor et al 2014).…”
mentioning
confidence: 99%
“…Attunement items were scaled from 0 (Not at All Sure) to 2 (Very Sure); Perceptions of Support items (Do/Do Not), Relationship Reaffirming Behavior Items, (Agree/Disagree), and Trust Items (Will/Will Not), were each binary and coded 0/1. Though this scale was originally used and validated on middle childhood and young adolescent samples (Kerns et al, 2000; Kim et al, 2015), recent work has shown evidence for predictive and convergent validity in middle and older adolescents (Van Ryzin and Leve, 2012; Kerns et al, 2015). Exploratory factor analyses on these items did not distinguish these facets from one another and they are therefore aggregated into a single scale; Cronbach’s alpha for the aggregated scale was 0.70.…”
Section: Methodsmentioning
confidence: 99%